Ocena rekultywacji leśnej zwałowiska odpadów po wydobyciu węgla kamiennego na przykładzie KWK "Brzeszcze" w Brzeszczach = Assessment of forest reclamation of a hard coal waste heap as exemplified by the "Brzeszcze" hard coal mine in Brzeszcze - Pająk, Marek; Krzaklewski, Wojciech; Gawełek, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present study assesses the forest reclamation of the hard coal waste heap at the "Brzeszcze" hard coal mine in Brzeszcze. The arborescent vegetation introduced at the waste heap is characterised by good vitality and quality and it fulfills its numerous functions, from protective to landscape ones. To a large extent, the proper growth and development of the introduced trees has been made possible by the correct execution of technical reclamation, particularly bringing the surface soil layer (40 cm) with proper volume and quality.
Keywords: zwałowisko; rekultywacja; roślinność drzewiasta; waste heap; reclamation; arborescent vegetation